2015
DOI: 10.1089/vbz.2014.1625
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiology of Tacaribe Serocomplex Viruses (Arenaviridae) Associated with Neotomine Rodents (Cricetidae, Neotominae) in Southern California

Abstract: The objective of this study was to advance our knowledge of the epizootiology of Bear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Evidence of mammarenavirus infection in rodents, bats and humans within the Americas has been previously documented in the USA, Columbia, Brazil and French Guiana [54][55][56][57][58][59][60][61][62][63][64][65]. A mammarenavirus seroprevalence rate of 2.5% was observed among wild rodents in Barbados during this study, which is comparable to seroprevalence rates observed in wild rodents from Turkey (2.4%), Italy (5.6%), the United Kingdom (5.8%) and the USA (3.1%) [66][67][68][69].…”
Section: Mammarenavirus Ifa Seropositive Rodentsmentioning
confidence: 99%
“…Evidence of mammarenavirus infection in rodents, bats and humans within the Americas has been previously documented in the USA, Columbia, Brazil and French Guiana [54][55][56][57][58][59][60][61][62][63][64][65]. A mammarenavirus seroprevalence rate of 2.5% was observed among wild rodents in Barbados during this study, which is comparable to seroprevalence rates observed in wild rodents from Turkey (2.4%), Italy (5.6%), the United Kingdom (5.8%) and the USA (3.1%) [66][67][68][69].…”
Section: Mammarenavirus Ifa Seropositive Rodentsmentioning
confidence: 99%
“…An exception is Tacaribe virus (TCRV) that infects Artibeus bats and may be vectored by insects [4]. NW arenaviruses from Northern America infect rodents from the subfamily Neotominae, whereas those from Latin American and the Caribbean infect rodents from the subfamiliy Sigmodontinae [5,6]. Old World (OW) arenaviruses are found in African rodents from the family Muridae subfamily Murinae [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%